The influence of the natural and technical geosystem on the dynamic processes in the functioning environment of the Dniester PSPP - Zyhar, Andrii (Human Geography Journal, 2023)
The aim is to describe the field methods for studying the impact of the Dniester PSPP natural and technical geosystem (NTGS) on dynamic processes in the environment of its operation. A comprehensive research methodology was used to analyse the field methods for studying the impact of the Dniester PSPP natural and technical geosystem on dynamic processes in the environment of its operation. The initial stage included an analysis of the results of previous scientific studies on the impact of hydraulic engineering facilities on the environment. This made it possible to take into account previous findings and identify existing knowledge in this area. Next, we carried out on-site (field) data collection, which included in-situ measurements and observations directly in the area of the research object. For this purpose, specialised data collection devices were used. Particular attention was paid to the statistical analysis of the data obtained, which allowed us to identify the relationships between various factors that affect the dynamic processes of the environment. In the 21st century, geography is becoming an even more important and responsible science due to the growth of global challenges, such as climate change, environmental management, population migration, and others. An integrated approach allows geographers to look at problems from different perspectives and develop comprehensive solutions. Modern technologies, such as geographic information systems (GIS), satellite imagery, remote sensing, etc., provide geographers with new opportunities for collecting, analysing and interpreting data, which helps to solve complex problems more efficiently. An example of the application of an integrated approach in studying the impact of the natural and technical geosystem of the Dniester cascade of HPPs and PSPs on dynamic processes. Scientific novelty. The research in the article allows us to expand the understanding of the specific problem of managing anthropogenic load in a natural and technical system. The analysis of the object being designed as a system containing two most important parts – technical and natural - makes the systems approach not a decoration, but a prerequisite for the work of a natural scientist: geographer, ecologist – an ally, an associate of the designer. Designing, creating an environment that is optimal for human life means designing such systems, structures, and technologies so that they are as closely related to the existing relationships in nature as possible.